Pengaruh Penambahan Seduhan Teh Hijau [Camelia Sinensis (Linn.) Kunze] Terhadap Aktivitas Antioksidan Sari Buah Apel (Pyrus Mallus L.) - Sumarnya, Ros; Permadi, Trisna; Sugiarti, Lilis (Jurnal Sains dan Teknologi Farmasi, 2012)
Effect of green tea brewed addition toward the antioxidant activity of apple juice, have been investigated by measuring free radical 1,1-Diphenyl-2-picrylhydrazyl catches by sample. Ratio of green tea brewed with apple juice was 4:1(T4A1), 3:1(T3A1), 2:1(T2A1) and 1:1(T1A1). Results showed that antioxidant activity of T4A1 (IC50=0,6214% v/v) are not different evident (p<0,05) than green tea brewed (IC50=0,6091% v/v).